Association Between Traumatic Brain Injury-Related Brain Lesions and Long-term Caregiver Burden. Issue 2 (March 2016) - Guevara, Andrea Brioschi; Demonet, Jean-Francois; Polejaeva, Elena; Knutson, Kristine M.; Wassermann, Eric M.; Grafman, Jordan; Krueger, Frank
Abstract : Objective: To investigate the association between traumatic brain injury (TBI)–related brain lesions and long-term caregiver burden in relation to dysexecutive syndrome. Setting: National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, Maryland. Participants: A total of 256 participants: 105 combat veterans with TBI, 23 healthy control combat veterans (HCv), and 128 caregivers. Outcome Measure: Caregiver burden assessed by the Zarit Burden Interview at 40 years postinjury. Design: Participants with penetrating TBI were compared with HCv on perceived caregiver burden and neuropsychological assessment measures. Data of computed tomographic scans (overlay lesion maps of participants with a penetrating TBI whose caregivers have a significantly high burden) and behavioral statistical analyses were combined to identify brain lesions associated with caregiver burden. Results: Burden was greater in caregivers of veterans with TBI than in caregivers of HCv. Caregivers of participants with lesions affecting cognitive and behavioral indicators of dysexecutive syndrome (ie, left dorsolateral prefrontal cortex and dorsal anterior cingulate cortex) showed greater long-term burden than caregivers of participants with lesions elsewhere in the brain. Conclusion and Implication: The TBI-related brain lesions have a lasting effect on long-term caregiver burden due to cognitive and behavioral factors associated with dysexecutive syndrome.